Navigating peer-influences in a large youth homeless shelter in North America. (January 2020) - Alschech, Jonathan; Taiwo-Hanna, Tolulola; Shier, Micheal L.
Highlights: Research shows that peer influences in the lives of youth experiencing homelessness are both a risk factor and a protective factor. Youth homeless shelters are a central intersection of risk and resilience factors The interviewed residents described various positive peer influences, such as growth and attainment of social skills due to the diversity of the peers and the productive challenges of living with almost a hundred roommates. The residents described various examples of negative peers and their negative influences, some saying socialization is a common main barrier to rehousing. Peers were described as suggesting opportunities to participate in illegal activities and substance misuse. Residents specify strategies for minimizing negative influences, for example concentrating on oneself rather than on others and taking one's time to observe others' behaviors and interactions so as to make better decisions about who to associate with and who to trust. Interviewees described some of the challenges involved, such as the difficulty to sever relationships with peers one came to perceive as negative Abstract: Background: This study explored how youth who reside in a large youth homeless shelter in North America view and navigate peer-influences in the shelter. Research shows that peer influences in the lives of youth experiencing homelessness are both a risk factor and a protective factor. In order to inform the development of shelter policies and interventions that reduce and contain peer influences that put the residents at risk while cultivating peer support and cohesion, a better understanding of the residents' views and insights regarding peer-influences is needed. Methods: Interviews (n = 27) were conducted with residents (aged 18–24) of a youth homeless shelter. Following a semi-structured open-ended interview guide, respondents were asked questions related to program outcomes and their experiences within the shelter that support those outcomes. One dominant factor emerging from the interview data analysis was the central role played by peer relationships and influences. Results: The residents described the shelter as housing two kinds of peer interactions. Perceived as positive peers' influences were described as pivotal for successfully transitioning into stable, sustainable housing. Perceived as negative peer influences, on the other hand, were described as a significant risk for one's wellbeing and trajectory. The interviewees disclosed strategies for navigating peer influences in the shelter, such as withdrawing from any social involvement with the other residents or only allowing for shallow ephemeral friendships, as well as some of the challenges involved, such as the difficulty to sever relationships with peers one came to perceive as negative.